2020
DOI: 10.1108/pr-06-2020-0407
|View full text |Cite
|
Sign up to set email alerts
|

Supportive organizational climate: a moderated mediation model of workplace bullying and employee well-being

Abstract: PurposeDrawing from conservation of resources theory, this study explores how perceived organizational support mitigates the adverse consequences of workplace bullying on employee well-being mediated through burnout.Design/methodology/approachThe data (N = 360) were collected from the hotel sector in Pakistan. Structural equation modeling (SEM) was employed to analyze the data.FindingsThe findings demonstrated that workplace bullying not only has a direct negative impact on employee well-being but it also indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 88 publications
4
70
0
Order By: Relevance
“…Various indigenous studies suggested that a negative workplace creates unfavorable consequences for individuals in Pakistani organizations. These signify the need to conduct further relevant studies to validate the theory of workplace bullying on employee performance (Naseer & Raja, 2019;Hayat &Afshari, 2020). In addition study by Ali et.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Various indigenous studies suggested that a negative workplace creates unfavorable consequences for individuals in Pakistani organizations. These signify the need to conduct further relevant studies to validate the theory of workplace bullying on employee performance (Naseer & Raja, 2019;Hayat &Afshari, 2020). In addition study by Ali et.…”
Section: Rationalementioning
confidence: 99%
“…Future studies can investigate the level of well-being environment, emotions with positive work circumstances .i.e. organization citizenship behaviors, positive emotions, supportive leadership style, and green HRM practices (Boswell et al, 2019, Hayat & Afshari, 2020, Shah et al, 2020& Fatima et al 2010. Finally, the current study was used the research instruments .i.e.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Given that culture has been described as one of the primary shapers of employee perception (Hayat and Afshari, 2020), understanding the impacts of leadership in different cultural contexts is argued to be insufficient without giving proper consideration to the relational aspect of leadership (Koveshnikov and Ehrnrooth, 2018). It is evident from previous literature that there is a clear need for a focus on the relational aspect of leadership in order to elucidate the mechanisms leading to organizational outcomes in contexts with distinct cultural values (Fairhurst and Uhl-Bien, 2012).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Proper modifications were made to fit the current research context. Supportive organizational climate comprised of 8 items and was adapted from (Hayat & Afshari, 2020). Leadership support was adopted from (Iqbal, Ehsan, Rizwan & Noreen, 2014), while commitment value co-creation was taken from (Järvi, Kähkönen & Torvinen, 2018).…”
Section: The Measurement Instrumentsmentioning
confidence: 99%